1990
DOI: 10.4315/0362-028x-53.7.558
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Shigella sonnei in Shredded Cabbage

Abstract: Commercially shredded cabbage distributed at the retail level is usually packaged under vacuum or in a modified atmosphere of nitrogen and carbon dioxide to suppress proliferation of aerobic spoilage microorganisms. The ability of Shigella sonnei to survive and grow in shredded cabbage packaged under these conditions was determined by the 3-tube most probable number procedure. After artificial inoculation with S. sonnei at one of three different levels, the shredded cabbage was packaged aerobically, under vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The attachment, behavior and survival of L. monocytogenes (Ijabadeniyi, Minnaar, & Buys, ), Shigella (Satchell, Stephenson, Andrews, Estela, & Allen, ), and S. aureus (Martin & Beelman, ) in fruits and vegetables have also been reported in different studies. Nevertheless, there is limited information on the ability of attachment, behavior and survival of other pathotypes of E. coli different to O157 as well as V. cholerae on fruits such as strawberries.…”
Section: Resultsmentioning
confidence: 91%
“…The attachment, behavior and survival of L. monocytogenes (Ijabadeniyi, Minnaar, & Buys, ), Shigella (Satchell, Stephenson, Andrews, Estela, & Allen, ), and S. aureus (Martin & Beelman, ) in fruits and vegetables have also been reported in different studies. Nevertheless, there is limited information on the ability of attachment, behavior and survival of other pathotypes of E. coli different to O157 as well as V. cholerae on fruits such as strawberries.…”
Section: Resultsmentioning
confidence: 91%
“…Another study showed that Sh. sonnei in shredded cabbage stored under vacuum or in modified atmosphere packaging conditions survived for several days when stored under room temperature or refrigeration conditions (Satchell, Stephenson, Andrews, Estela, & Allen, ). Erickson et al () also reported that Sh.…”
Section: Resultsmentioning
confidence: 99%
“…sonnei was epidemiologically linked to outbreaks in which carrots, coleslaw, potato salad, and chicken salad were involved as transmission vehicles. Nonetheless, salad samples stored at room temperature experienced drop in pH values, and this might have led to a decline in Shigella numbers (Satchell et al, ; Warren, Parish, & Schneider, ). The initial numbers of MAB in coleslaw inoculated with Salmonella significantly declined ( p < .05) by 1.2–1.9 log CFU/g at the end of storage time at all tested temperatures (Table C).…”
Section: Resultsmentioning
confidence: 99%
“…Shigella is able to survive on produce packaged under vacuum or modified atmosphere. [112] investigated the survival of S. sonnei in shredded cabbage packaged under vacuum or in a modified atmosphere of nitrogen and carbon dioxide when stored at room temperature or under refrigeration.…”
Section: Growth Potential Of Salmonella and Shigellamentioning
confidence: 99%